Electronic Participation 6th IFIP WG 8.5 International Conference, ePart 2014, Dublin, Ireland, September 2-3, 2014, Proceedings - Tambouris, Efthimios; Macintosh, Ann.; Bannister, Frank Edward; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 6th IFIP WG 8.5 International Conference on Electronic Participation, ePart 2014, held in Dublin, Ireland, in September 2014. The 11 revised full papers presented were carefully reviewed and selected from 20 submissions. The papers have been organized in the following topical sections: social media; review and analysis; engaging citizens online; and software platforms and evaluation.
Social Media vs. Traditional Internet Use for Community Involvement: Toward Broadening Participation -- Leveraging European Union Policy Community through Advanced Exploitation of Social Media -- Genres of Participation in Social Networking Systems: A Study of the 2013 Norwegian Parliamentary Election -- Starting a Conversation: The Place of Managers in Opening Discussions in Communities of Practice -- The Role of a Political Party Website: Lessons Learnt from the User Perspective -- Conceptualising Trust in E-Participation Contexts -- Information Technology in eParticipation Research: A Word Frequency Analysis -- New Ways of Deliberating Online: An Empirical Comparison of Network and Threaded Interfaces for Online Discussion -- Engaging Citizens in Policy Issues: Multidimensional Approach, Evidence and Lessons Learned -- A Goal Matching Service for Facilitating Public Collaboration Using Linked Open Data -- Evaluation of an E-participation Project: Lessons Learned and Success Factors from a Cross-Cultural Perspective.
Keywords: Computers and civilization; Application software; Computers; Computers and Society; Computer Appl. in Administrative Data Processing; Information Systems and Communication Service